Assessment of Bryophyllum pinnatum mediated Ag and ZnO nanoparticles as efficient antimicrobial and cytotoxic agent - Huma Noor; Asma Ayub; Erum Dilshad; Tayyaba afsar; Suhail Razak; Fohad Mabood Husain; Janeen H. Trembley (Scientific Reports, 2024)
Abstract Bryophyllum pinnatum is used to cure infections worldwide. Although the flavonoids of this plant are well known, it is still unknown how much of the plant’s Ag and ZnO nanoparticles are beneficial. In the current research work, silver and zinc oxide nanoparticles were prepared using Bryophyllum pinnatum extract. The synthesized particles were characterized by UV-visible spectroscopy, SEM, EDS, XRD and FTIR. Synthesized particles were subjected to evaluation of their bactericidal and antifungal activity at various doses. Uv vis spectra at 400 nm corresponding to AgNPs confirmed their synthesis. Strong peaks in the EDS spectra of Ag and ZnO indicate the purity of the sample. The scanning electron microscopic images of ZnONPs showed a size of about 60 nm ± 3 nm, which demonstrated the presence of triangular-shaped ZnO nanoparticles. Green synthesized nanoparticles showed bactericidal activity against both Gram-positive (Micrococcus luteus, Staphylococcus aureus, Bacillus subtilis) and Gram-negative (Agrobacterium tumifaciens, Salmonella setubal, Enterobacter aerogenes) strains. AgNPs proved to be more effective against Gram-negative bacterial strains compared to Gram-positive owing to MIC values (10 ppm and 20 ppm respectively). Whereas, ZnONPs were found more effective against Gram-positive bacteria with lower MIC values (10 ppm) as compared to Gram-negative ones (20 ppm). Also, the synthesized nanoparticles exhibited moderate dose-dependent antifungal activity against tested fungal strains ranging from 10 to 70%. Cytotoxicity of nanoparticles was found significant using Brine shrimp’s lethality assay with IC50 values of 4.09 ppm for AgNPs, 13.72 ppm for ZnONPs, and 24.83 ppm for plant extract. Conclusively, Ag and ZnO nanoparticles were more effective than plant extract and AgNPs had higher activities than those of ZnONPs. Further research is warranted to explore the precise mechanism of action and the potential applications of these nanoparticles in the medical field.